Infinite series

Algebra Level 3

Given that ζ ( 2 ) = π 2 6 \zeta(2)=\frac{{\pi}^2}{6} .

S = 1 + 1 3 2 + 1 5 2 S=1+\frac{1}{3^2}+\frac{1}{5^2}……\infty

Find S S .


The answer is 1.23.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Noel Lo
Jun 15, 2015

1 + 1 3 2 + 1 5 2 + . . . . = ( 1 + 1 2 2 + 1 3 2 + . . . . ) ( 1 2 2 + 1 4 2 + 1 6 2 + . . . ) 1 + \frac{1}{3^2} + \frac{1}{5^2} +.... = (1+\frac{1}{2^2} + \frac{1}{3^2} + ....) - (\frac{1}{2^2} + \frac{1}{4^2} +\frac{1}{6^2}+...)

= π 2 6 1 2 2 ( π 2 6 ) = π 2 6 1 4 ( π 2 6 ) = 3 4 ( π 2 6 ) = π 2 8 = 1.23 \frac{\pi^2}{6} - \frac{1}{2^2} (\frac{\pi^2}{6} )= \frac{\pi^2}{6} - \frac{1}{4} (\frac{\pi^2}{6}) = \frac{3}{4}(\frac{\pi^2}{6}) = \frac{\pi^2}{8} = \boxed{1.23} .

Observe that

S = ζ ( 2 ) n = 1 1 ( 2 n ) 2 = ζ ( 2 ) 1 4 n = 1 1 n 2 = ζ ( 2 ) 1 4 ζ ( 2 ) = 3 4 ζ ( 2 ) 1.2337 S = \zeta(2) - \sum_{n=1}^{\infty} \frac{1}{(2n)^2} = \zeta(2) - \frac{1}{4} \sum_{n=1}^{\infty} \frac{1}{n^2} = \zeta(2) - \frac{1}{4} \zeta(2) = \frac{3}{4} \zeta(2) \approx 1.2337

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...